2013
DOI: 10.1097/01.epx.0000427043.99834.a4
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection

Abstract: Infection with H. pylori is declining among healthy individuals of Al Madinah, Saudi Arabia. Infection is acquired at an early age and reaches up to 36.9% as age advances. The risk of H. pylori seropositivity was related to socioeconomic, lifestyle, and environmental factors. A nationwide epidemiological study is warranted to determine the seroprevalence of H. pylori in Saudi Arabia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 24 publications
2
29
0
3
Order By: Relevance
“…The risk factors for H. pylori infection have been investigated in several countries of the MENA region. Age (>10 years), low socioeconomic status, low level of education, married participants, number of residents per household, bed sharing, drinking municipal or tank water, eating outside the home, living in rural areas, smoking, alcohol consumption, type 2 Diabetes Mellitus, chronically dyspeptic patients, eating raw vegetables or spicy food and having two affected parents were identified as risk factors in the majority of studies [17,28,31,34,35,[38][39][40].…”
Section: Risk Factors For H Pylori Infectionmentioning
confidence: 99%
“…The risk factors for H. pylori infection have been investigated in several countries of the MENA region. Age (>10 years), low socioeconomic status, low level of education, married participants, number of residents per household, bed sharing, drinking municipal or tank water, eating outside the home, living in rural areas, smoking, alcohol consumption, type 2 Diabetes Mellitus, chronically dyspeptic patients, eating raw vegetables or spicy food and having two affected parents were identified as risk factors in the majority of studies [17,28,31,34,35,[38][39][40].…”
Section: Risk Factors For H Pylori Infectionmentioning
confidence: 99%
“…Moderate [404][405][406][407][408][409][410][411][412][413][414][415] Waterborne NE Helicobacter spp.…”
Section: Ne Water Based Nementioning
confidence: 99%
“…[24] In contrast, some studies reported that H. pylori -positive individuals had significantly higher intake of raw vegetables compared to negative ones which may be contributed intransmission of bacteria through contaminated foods probably due to poor hygiene conditions of study population. [1617] Moreover, the results of some clinical trials represented the beneficial effects of dietary factors such as Omega-3 polyunsaturated fatty acids or sulforaphane-rich broccoli sprouts in inhibition of H. pylori colonization, attenuation of H. pylori -induced inflammation, and modifying blood lipid distortion among H. pylori - infected patients. [2526] These finding may strengthen the possible role of diet in H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…[1415] On the other hand, some reports indicated that diet may increase the susceptibility to H. pylori infection through contamination of foods with H. pylori bacterium. [1617] The relationship of diet-infection is still unclear and providing further evidences to elucidate this association seems to be crucial.…”
Section: Introductionmentioning
confidence: 99%